MicroRNA-Mediated Regulation of Ionizing Radiation Responses: Mechanisms and Advances in Clinical Translation - Keying Lian; Quan Ma; Xiao Mo; Zhisheng Jiang; Yun Ma (Current Issues in Molecular Biology, 2026)
Ionizing radiation can induce DNA damage through direct or indirect mechanisms and activate the DNA damage response network, thereby influencing cellular repair, cell cycle regulation and cell fate determination. MicroRNAs (miRNAs), as key post-transcriptional regulatory factors, play a vital role in modulating the radiation response and cell fate. This review summarizes radiation-induced changes in miRNA expression and the molecular regulatory mechanisms they mediate, and further discusses recent advances in their application in the assessment of radiation damage, the prediction of radiotherapy response, and therapeutic interventions. Although miRNAs possess significant translational value, their multi-target regulatory characteristics, tissue- and environment-dependence, as well as limitations in clinical detection and delivery systems, continue to hinder their application. In the future, the integration of multi-omics technologies, artificial intelligence analysis and precision delivery strategies is expected to further elucidate the miRNA-mediated radiation response network and advance their application in precision radiology.